IMF Staff papers : Volume 3 No. 1. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1953)
This paper discusses the causes of the imbalance of international payments. Under the forces of supply and demand, gold came to have a certain value in relation to goods, which enabled it to function smoothly as a medium of reserve and settlement. This value varied somewhat from time to time under the influence of new discoveries or the exhaustion of existing sources. Of all the particular imbalances in the international payments pattern, that between the dollar and other currencies is the greatest. Unfortunately, it is extremely difficult to measure the amount of imbalance existing. Europe has made considerable and, to some extent, successful efforts to expand direct sales to the United States. It is in the sphere of finished manufactures principally that one could hope for an expansion of exports by an organized export drive or currency devaluation, other categories of goods depending more on the level of US production and national income.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet